Citizen participation in public administration: Views from Lebanon - AbouAssi, Khaldoun; Antoun, Randa; Nabatchi, Tina (2013)
This article examines citizen participation in Lebanon. Specifically, we apply the International Association for Public Participation Spectrum of Public Participation (2007) and use survey, interview, and archival data to understand how and why Lebanese government agencies use citizen participation. In addition to reviewing survey data, we present short cases about citizenparticipation in the three Lebanese agencies. Our findings indicate that the majority of public agencies in Lebanon use basic forms of citizen participation that span the inform-consult categories on the IAP2 spectrum. The article concludes with a discussion about the challenges of and prospects for citizen participation in the Lebanese publicsector. - Reproduced.
Keywords: Workers participation; Public administration